2021
DOI: 10.1007/s00467-021-04972-6
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis (HD) dose and ultrafiltration rate are associated with survival in pediatric and adolescent patients on chronic HD—a large observational study with follow-up to young adult age

Abstract: Background Hemodialysis (HD) dose targets and ultrafiltration rate (UFR) limits for pediatric patients on chronic HD are not known and are derived from adults (spKt/V>1.4 and <13 ml/kg/h). We aimed to characterize how delivered HD dose and UFR are associated with survival in a large cohort of patients who started HD in childhood. Methods Retrospective analysis on a cohort of patients <30 years, on chronic HD since childhood (<19 years), having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…Additionally, dialysis dose in terms of spKt/V and fluid balance in terms of ultrafiltration (UF) rate prove to be crucial in classifying the data into high-risk (cluster 1) and low-risk (cluster 2) groups. By analysing the cluster-wise distributions, we notice that the high-risk cluster is characterised by lower values of albumin, dialysis dose, and ultrafiltration, in agreement with previous studies (Gotta et al, 2020(Gotta et al, , 2021Movilli et al, 2007).…”
Section: Qualitative Results On Hemodialysis Datasupporting
confidence: 91%
See 3 more Smart Citations
“…Additionally, dialysis dose in terms of spKt/V and fluid balance in terms of ultrafiltration (UF) rate prove to be crucial in classifying the data into high-risk (cluster 1) and low-risk (cluster 2) groups. By analysing the cluster-wise distributions, we notice that the high-risk cluster is characterised by lower values of albumin, dialysis dose, and ultrafiltration, in agreement with previous studies (Gotta et al, 2020(Gotta et al, , 2021Movilli et al, 2007).…”
Section: Qualitative Results On Hemodialysis Datasupporting
confidence: 91%
“…We now investigate qualitatively the clustering obtained by VaDeSC when applied to the Hemodialysis dataset. The true structure of this data is unknown, however several studies have suggested a stratification of patients according to age and dialysis doses (Gotta et al, 2021). We compute the optimal number of clusters using grid-search by measuring the timeto-event prediction performance.…”
Section: Qualitative Results On Hemodialysis Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Echocardiography revealed moderate/severe systolic dysfunction of the left ventricle, impaired diastolic dysfunction (pseudonormal transmitral pattern), low-normal right ventricle systolic function, moderate pulmonary systolic pressure, and a large amount of pericardial fluid. The clinical picture maintained despite supplemental daily hemodialysis sessions performed with maximal ultrafiltration (13 mL/kg/h) [16,17]. She was transferred to a COVID-19 designated hospital for isolation and specific treatment.…”
Section: Case Presentationmentioning
confidence: 99%